ANALISIS PENGARUH IKLIM ORGANISASI, SERVANT LEADERSHIP, DAN INTRINSIC MOTIVATION TERHADAP ORGANIATIONAL CITIZENSHIP BEHAVIOR (OCB) PADA PT. BIOMETRIK CITRA SOLUSI - Lailatul Musyaffaah (Universitas Nahdlatul Ulama Sidoarjo, 2022)
The increasingly fierce business competition makes companies have to make the right strategy within the company, especially strategies related to improving employee performance. The aim of this research is to find out how much influence organizational climate, servant leadership, and intrinsic motivation have on organizational citizenship behavior (OCB). This study uses quantitative research methods and SPSS data processing using regression analysis and 36 respondents. The results of data processing show that there is an influence of organizational climate, servant leadership, intrinsic motivation on Organizational Citizenship Behavior (OCB) both simultaneously and partially.